Population Genetic Structure and Gene Expression Plasticity of the Deep-Sea Vent and Seep Squat Lobster Shinkaia crosnieri - Xiao, Yao; Xu, Ting; Sun, Jin; Wang, Yan; Wong, Wai Chuen; Kwan, Yick Hang; Chen, Chong; Qiu, Jian-Wen; Qian, Pei-Yuan (Frontiers in Marine Science, 2020)
Shinkaia crosnieri (Decapoda: Munidopsidae) is a squat lobster that dominates both deep-sea hydrothermal vent and methane seep communities in the Western Pacific. Previous studies comparing S. crosnieri living in these two types of habitats have suffered from methodological and/or sample size limits. Here, using transcriptome-wide single nucleotide polymorphisms (SNPs) markers from 44 individuals of S. crosnieri, we reveal the extent of genetic connectivity between a methane seep population in the South China Sea and a hydrothermal vent population in the Okinawa Trough, as well as their signatures of local adaptation. Analysis of differentially expressed genes (DEGs) between these two populations and population-specific genes (PSGs) revealed that a large number of unigenes, such as cytochrome P450 (CYP), glutathione S-transferase (GST) and peroxiredoxin 6 (Prdx6) related to oxidoreductase, and sulfur dioxygenase (ETHE1) and chondroitin 4-sulfotransferase 11 (CHST11) related to sulfur metabolism, showed opposite expression patterns in these two populations. Data subsampling in this study revealed that at least five individuals of S. crosnieri per site are required to generate reliable results from the differential gene expression analysis. Population genetic analyses based on 32,452 SNPs revealed clear genetic differentiation between these two populations with an FST value of 0.07 (p < 0.0005), and physical oceanographic modeling of the ocean currents in middle and deep layers also suggests a weak connection between these two sites. Analysis of outlier SNPs revealed 345 unigenes potentially under positive selection, such as sarcosine oxidase/L-pipecolate oxidase (PIPOX), alanine-glyoxylate transaminase/serine-glyoxylate transaminase/serine-pyruvate transaminase (AGXT), and Cu-Zn superoxide dismutase (SOD1). Among the differentially expressed genes and genes with amino acid substitutions between the two sites are those related to oxidation resistance and xenobiotic detoxification, indicating local adaptation to the specific environmental conditions of each site. Overall, exploring the population structure of S. crosnieri using transcriptome-wide SNP markers resulted in an improved understanding of its molecular adaptation and expression plasticity in vent and seep ecosystems.